Degradation of fly ash concrete under the coupled effect of carbonation and chloride aerosol ingress. (November 2016) - Liu, Jun; Qiu, Qiwen; Chen, Xiaochi; Wang, Xiaodong; Xing, Feng; Han, Ningxu; He, Yijian
Highlights: Carbonation affects the chloride profile in concrete under chloride aerosol attack. The chloride binding capacity can be reduced by the presence of carbonation. Carbonation increases the rate of chloride diffusion for chloride aerosol ingress. Chloride aerosol ingress reduces the carbonation depth and increases the pH value. The use of fly ash in concrete enhances the resistance of chloride aerosol ingress. Abstract: This paper presents an experimental investigation regarding the coupled effect of carbonation and chloride aerosol ingress on the durability performance of fly ash concrete. Test results demonstrate that carbonation significantly affects the chloride ingress profile, reduces the chloride binding capacity, and accelerates the rate of chloride ion diffusion. On the other hand, the carbonation rate of fly ash concrete is reduced by the presence of chlorides aerosol. The interaction nature between concrete carbonation and chloride aerosol ingress is also demonstrated by the microscopic analysis results obtained from scanning electron microscope and mercury intrusion porosimetry.